Preparing future educational psychologists to support schoolchildren's cognitive activity through project-based learning (Gumilyov Journal of Pedagogy, 2025)
This article examines the problems and prospects regarding the readiness of future educational psychologists to support the cognitive activity of schoolchildren through project-based activities. The study was conducted to determine the effectiveness of the process of preparing future educational psychologists to support the cognitive activity of schoolchildren through project-based activities. The main ideas of the study are: to determine the main theoretical characteristics of the readiness of educational psychologists to support the cognitive activity of schoolchildren through project activities,and to establish the possibility of increasing the readiness of future educational psychologists to support the cognitive activity of schoolchildren through project activities. The scientific and practical significance of the study lies in the expansion of theoretical knowledge and the development of scientifically based recommendations. The proposed model and development program are confirmed by the results of the study: the level of readiness of future educational psychologists in the experimental group to support the cognitive activity of schoolchildren through project activities has significantly increased, while the control group, which did not receive such training, showed minimal growth indicators; the school experiment also confirmed that project activities accompanied by future educational psychologists who have undergone additional training significantly increases the level of cognitive activity of schoolchildren. Recommendations have been developed for the implementation of the proposed model in pedagogical practice in order to increase the level of readiness of educational psychologists to support the cognitive activity of schoolchildren through project activities and to develop the cognitive activity of schoolchildren.